Answer:
Any equation of a line having a slope of 1/2.
Step-by-step explanation:
It appears that the question gives answer choices and this problem could have many solutions, but parallel lines have equal slopes. The slope of this line is 1/2 since it is in y=mx+b form where m is the slope. So a few examples of equations of lines parallel to the given equation would be y = 1/2x - 5 or y = 1/2x + 10 etc.
A single, six-sided die is rolled. Find the probability of rolling an even
number or a number less than 3
Answer:
5/6 (if including 3) 4/6 (not including 3)
Step-by-step explanation:
1 and 2 are less than 3
4 and 6 are even
that leaves 5 and 3.
so 4 of the numbers are even or less than 3
Probability of rolling even number or number less than 3 is 2/3.
What is probability?Probability is defined by the possibility of the event to happen which is ratio of no. of favorable outcomes and the total no. of outcomes.
Probability of event = P(E) = No. of favorable outcomes/Total No. of outcomes
Here given that the dice is fair and six-sided is rolled.
Total no. of outcomes by rolling the dice=6 i.e. {1,2,3,4,5,6}
No. of favorable outcomes of getting even no. =3 i.e. {2,4,6)
Probability of rolling an even no.=P(even)= No. of favorable outcomes/Total No. of outcomes = 3/6
No. of favorable outcomes of getting no. less than 3 =2 i.e. {1,2}
Probability of rolling no. less than 3=P(<3) =No. of favorable outcomes/Total No. of outcomes = 2/6
No. of favorable outcomes of getting even no and number less than 3 =1 i.e. {2}
Probability of rolling an even no. and no. less than 3 =P(even and <3) = P(even ∩ <3)= No. of favorable outcomes/Total No. of outcomes = 1/6
As we know P(A∪B)=P(A)+P(B)-P(A∩B)
Probability of rolling an even no.or no. less than 3 = P(even or <3) = P(even ∪ <3)= P(even)+P(<3)-P(even ∩ <3)
=(3/6)+(2/6)-(1/6)
=4/6
=2/3
Therefore probability of rolling even number or number less than 3 is 2/3.
Learn more about probability
here: https://brainly.com/question/14192140
#SPJ2
Find the value of -36+(-9)+14+(-31)-(-66)
Answer:
4
Step-by-step explanation:
-36-9+14-31+66
=4
Since + - = - and - - = +
which of the following is a factor of 6x^3 + 6?
a) x - 1
b) x + 1
c) x² - 2x + 1
d) x² + x + 1
Answer:
B
Step-by-step explanation:
Given
6x³ + 6 ← factor out 6 from each term
= 6(x³ + 1)
x³ + 1 is a sum of cubes and factors as
x³ + 1 = (x + 1)(x² - x + 1)
Hence
6x³ + 6 = 6(x + 1)(x² - x + 1)
With factor (x + 1) → B
Answer:
b) x + 1
Step-by-step explanation:
you can either
1) take (6x³ + 6) and divide by all the choices to see which one gives you a factor. You will realize that if you divide this by option b, you will be able to factorize the equation as follows:
(6x³ + 6) = 6(x+1)(x²−x+1)
Hence option b is a factor
or
2) (my preferred method), utilize the properties of functions and roots.
Let function f(x) = 6x³ + 6
any value of a which gives f(a) = 0 is a root , i.e (x-a) is a factor.
In this case, lets consider option b
let x + 1 = 0 -------> or x = -1
substitute this into the function f(x)
f(-1) = 6 (-1)³ + 6
f(-1) = -6 + 6 = 0
hence x = -1 is a root , or (x+1) is a factor.
as a sanity check, lets try choice a) x -1
let x - 1 = 0 -------> or x = +1
substitute this into the function f(x)
f(1) = 6 (1)³ + 6
f(1) = 6 + 6 = 12 ≠0
hence x = 1 is NOT a root , or (x-1) is NOT a factor.
You can do the same for c and d and find that they too are NOT factors.
There is a total of 270 men women and children on a train the ratio of men to women is 4:5 the ratio of women to children is 10:9 how many men are on the train
Answer:
80
Step-by-step explanation:
Let's say M is the number of men, W is the number of women, and C is the number of children.
M + W + C = 270
M/W = 4/5
W/C = 10/9
We have three equations and three variables, so we can solve this. Let's use substitution.
W = 5/4 M
C = 9/10 W
Substitute into the first equation:
M + 5/4 M + 9/10 W = 270
Substitute again:
M + 5/4 M + 9/10 (5/4 M) = 270
Solve:
M + 5/4 M + 9/8 M = 270
8/8 M + 10/8 M + 9/8 M = 270
27/8 M = 270
M = 80
There are 80 men on the train.
What is the greatest common factor of the polynomial 40x^7+135x^4+5x^4
5x^4
Step-by-step explanation:
simply we take 5x^4 bec. it can be divided by 40 and 135
Osvoldo has a goal of getting at least 30%, percent of his grams of carbohydrates each day from whole grains. Today, he ate 220 grams of carbohydrates, and 55grams were from whole grains.
Did Osvoldo meet his goal? How many grams of whole grain did he eat?
Answer:
Osvoldo does not meet his goal
He had to have eaten at least 66 grams of whole grains to meet his goal.
Step-by-step explanation:
step 1
Find out the 30% of the grams of carbohydrates that Osvoldo ate today
Remember that
30%=30/100=0.30
so
0.30(220)=66 grams
step 2
Compare the 30% of the grams of carbohydrates that Osvoldo ate today with the 55 grams of whole grains
we know that
To Osvoldo meet his goal the 55 grams of whole grain must be greater than or equal to the 30% of the grams of carbohydrates that Osvoldo ate today
55 < 66
therefore
Osvoldo does not meet his goal
He had to have eaten at least 66 grams of whole grains to meet his goal.
Oscar gained x pounds within the last year. he weighed 96 pounds last year. which expressions correctly describes his current weight?
a. 96 - x
b. 96 + x
c. 96x
d. 96/x
Answer:
b
becasue to find his current weight you would use what you know and the amount of lbs he added (represented as x)
96 + x
Step-by-step explanation:
Solve this radical equation (square root of x+11)-x=-1
[tex]\bf \sqrt{x+11}-x=-1\implies \sqrt{x+11}=x-1\implies \stackrel{\textit{squaring both sides}}{(\sqrt{x+11})^2=(x-1)^2} \\\\\\ x+11=\stackrel{\mathbb{F~O~I~L}}{x^2-2x+1}\implies 11=x^2-3x+1\implies 0=x^2-3x-10 \\\\\\ 0=(x-5)(x+2)\implies x= \begin{cases} 5\\ -2 \end{cases}[/tex]
Gives x = -5 or x = 2.
Learn how to solve radical equations step by step by isolating terms and squaring, resulting in solutions to the given equation.
To solve the equation (square root of x+11)-x=-1, follow these steps:
Isolate the square root term: square root of x+11=-1+xSquare both sides to eliminate the square root: x+11 = x^2+2x+1Rearrange the equation and solve the quadratic: x^2+x-10=0, which gives x = -5 or x = 2
(1/x)+(1/x-y)
Please solve this question. I will mark you brainliest.
Answer:
[tex]\frac{2x-y}{x(x-y)}[/tex]
Step-by-step explanation:
To express as a single fraction
multiply numerator/denominator of [tex]\frac{1}{x}[/tex] by (x - y) and
multiply numerator/ denominator of [tex]\frac{1}{x=y}[/tex] by x
= [tex]\frac{x-y}{x(x-y)}[/tex] + [tex]\frac{x}{x(x-y)}[/tex]
Add the numerators leaving the denominator
= [tex]\frac{2x-y}{x(x-y)}[/tex]
What is the solution
Answer:
y ≥ 14.
Step-by-step explanation:
y - 27 ≥ -13 Add 27 to both sides:
y ≥ 14 (answer).
For this case we must find the solution of the following inequality:
[tex]y-27 \geq-13[/tex]
We must add 27 to both sides of the inequality:
[tex]y \geq-13 + 27[/tex]
We know that different signs are subtracted and the sign of the major is placed.[tex]y \geq14[/tex]
So, the solution is [tex]y \geq14[/tex]
Answer:
Option C
whats the are of this figure?!?
Answer:
The area is 5.5 cm squared.
Step-by-step explanation:
To find the area, you have to find the areas of the rectangle and the triangle separately and then add your two values together.
The formula for the area of a rectangle is as follows:
[tex]A=lw[/tex]
In this formula, "l" refers to length and "w" refers to width.
As shown in the diagram, your length is 1.5 cm and your width is 2 cm.
Simply plug these numbers into the formula and simplify.
[tex]A=1.5*2\\A=3[/tex]
The area of the rectangle is 3 cm squared.
Next, find the area of the triangle. The formula for the area of a triangle is as follows:
[tex]A=\frac{1}{2} bh[/tex]
In this formula, "b" refers to the measure of the base and "h" refers to the measure of the height.
Your base (b) is 2 cm.
To find your height, subtract the length of the rectangle (1.5 cm) from the total length of the shape (4 cm). This will give you a height of 2.5 cm.
Next, plug your values into the formula and simplify.
[tex]A=\frac{1}{2} *2*2.5\\A=1*2.5\\A=2.5[/tex]
The area of the triangle is 2.5 cm squared.
Add the area of the rectangle (3 cm squared) to the area of the triangle (2.5 cm squared), and you have the area of the entire figure (5.5 cm squared).
Note: Carlos' mistake in the problem is that he forgot to subtract the length of the rectangle from the length of the entire shape, and incorrectly used 4 cm as his height for the triangle rather than 2.5 cm.
Enter a recursive rule for the geometric sequence.
2,−6,18,−54,...
Answer:
[tex]a_n=-3a_{n-1}[/tex] where [tex]a_1=2[/tex]
Step-by-step explanation:
Recursive means you want to define a sequence in terms of other terms of your sequence.
The common ratio is what term divided by previous term equals.
The common ratio here is -6/2=18/-6=-54/18=-3.
Or in terms of the nth and previous term we could say:
[tex]\frac{a_n}{a_{n-1}}=r[/tex]
where r is -3
[tex]\frac{a_n}{a_{n-1}}=-3[/tex]
Multiply both sides by the a_(n-1).
[tex]a_n=-3a_{n-1}[/tex] where [tex]a_1=2[/tex]
Answer:
see explanation
Step-by-step explanation:
A recursive rule allows us to obtain any term in the sequence from the previous term.
These are the terms of a geometric sequence with common ratio r
r = - 6 ÷ 2 = 18 ÷ - 6 = - 54 ÷ 18 = - 3
Thus to obtain a term in the sequence multiply the previous term by - 3
[tex]a_{n+1}[/tex] = - 3 [tex]a_{n}[/tex] with a₁ = 2
Inverse of f(x)=3x-4
Answer:
[tex]\large\boxed{f^{-1}(x)=\dfrac{x+4}{3}=\dfrac{1}{3}x+\dfrac{4}{3}}[/tex]
Step-by-step explanation:
[tex]f(x)=3x-4\to y=3x-4\\\\\text{exchange x to y and vice versa}\\\\x=3y-4\\\\\text{solve for y}\\\\3y-4=x\qquad\text{add 4 to both sides}\\\\3y=x+4\qquad\text{divide both sides by 3}\\\\y=\dfrac{x+4}{3}[/tex]
Ir x represents a postive
number, select all expressions
whose valve is greater than X.
A.(1 - 1-4)x
B.(1 + 1/4)x
C. 7/8x
D. 9/8x
Answer:
I think it may be B, but double check
Answer:
B and D
Step-by-step explanation:
Considering the multiple choices and let us assume that x = 2,
Option A would be equal to [tex]\frac{3}{4}x[/tex],
so if x = 2, then;
[tex]\frac{3}{4}x[/tex] = 1.5 (which is less than x)
Option B would give [tex]\frac{5}{4} x[/tex],
so if x = 2, then;
[tex]\frac{5}{4} x[/tex] = 2.5 ( which is greater than x)
From option C,
[tex]\frac{7}{8} x[/tex] = 1.75 (which is less than x)
From option D,
[tex]\frac{9}{8} x[/tex] = 2.25 ( which is greater than x)
So, options B and D are expressions whose values are greater than x.
You deposit $5000 in an account earning 8% interest compounded monthly. How much will you have in the account in 15 years?
[tex]\bf ~~~~~~ \textit{Compound Interest Earned Amount} \\\\ A=P\left(1+\frac{r}{n}\right)^{nt} \quad \begin{cases} A=\textit{accumulated amount}\\ P=\textit{original amount deposited}\dotfill &\$5000\\ r=rate\to 8\%\to \frac{8}{100}\dotfill &0.08\\ n= \begin{array}{llll} \textit{times it compounds per year}\\ \textit{monthly, thus twelve} \end{array}\dotfill &12\\ t=years\dotfill &15 \end{cases}[/tex]
[tex]\bf A=5000\left(1+\frac{0.08}{12}\right)^{12\cdot 15}\implies A=5000(1.00\overline{66})^{180}\implies A\approx 16534.61[/tex]
please answer this.
Also if you can, please answer my other question its very simmilar
For this case we have that a percentage equivalent to[tex]\frac {1} {8}[/tex]is given by:
[tex]x = \frac {1} {8} * 100 =[/tex] 12.5%
Then, according to the steps, it is observed that Harriet made an incorrect division, deboa multiply. So, the second step is the wrong one.
Answer:
Option B
The figure shows two similar triangles:
Which two sets of angles are corresponding angles?
What is the measure of angle E, in degrees?
The answer is 84 degrees because d and f both are 48 degrees so that adds up to 96. So that means you add 84 plus 96 which is 180 so the answer is 84 degrees.
Answer. The answer is 84
In the triangle, BC is the length of the mid-segment. Find the length of DE.
if f(x) = 3x - 2 and g(x) = 2x + 1, find (f - g)(x)
Answer:
(f-g)(x) = x-3
Step-by-step explanation:
Given
f(x) = 3x-2
and
g(x) = 2x+1
We have to find (f-g)(x)
So,
(f-g)(x) = f(x)-g(x)
= 3x-2 - (2x+1)
= 3x-2-2x-1
=x-3
Hence,
(f-g)(x) = x-3
Answer:
( f - g ) ( x ) = x - 3
Step-by-step explanation:
We are to find [tex] ( f - g ) ( x ) [/tex] given that [tex] f ( x ) = 3 x - 2 [/tex] and [tex] g ( x ) = 2 x + 1 [/tex].
So basically we have to subtract the function g from function f.
[tex] ( f - g ) ( x ) = f(x) - g(x) [/tex]
Substituting the given functions in the above equation to get:
[tex] ( f - g ) ( x ) = (3x - 2) - (2 x + 1 ) [/tex]
[tex] ( f - g ) ( x ) = 3x - 2 - 2 x - 1 [/tex]
[tex] ( f - g ) ( x ) = 3x - 2 x - 2 - 1 [/tex]
[tex] ( f - g ) ( x ) = x - 3 [/tex]
mk
---, for m = 6 and k = 2
m+k
So you're asking to evaluate this equation?
mk/m+k for m = 6 and k = 2
Lela purchased three mechanical pencils and a notebook that cost five dollars per purchase totaled $11 how much was each pencil use P to represent the cost of each pencil
Answer: 3p+5=11
Step-by-step explanation:
3p+5=11
-5 -5
3p=6
3p/3=6/3
P=2
$2
The cost of each pencil is $2.
What is a word problem?A word problem is a verbal description of a problem situation. It consists of few sentences describing a 'real-life' scenario where a problem needs to be solved by way of a mathematical calculation.
For the given situation,
Number of pencils = 3
Number of notebook = 1
Cost of a notebook = $5
Total cost = $11
Let number of pencil be p.
Lela purchased three mechanical pencils and a notebook is
⇒ [tex]3p+5=11[/tex]
⇒ [tex]3p=11-5[/tex]
⇒ [tex]3p=6[/tex]
⇒ [tex]p=\frac{6}{3}[/tex]
⇒ [tex]p=2[/tex]
Hence we can conclude that the cost of each pencil is $2.
Learn more about word problems here
brainly.com/question/20594903
#SPJ2
What are the solutions of the equation x4 - 9x2 + 8 = 0? Use u substitution to solve.
A. x = 1 and x = 2sqrt2
B. x=+/-1 and x = +/-2sqrt2
C. x=+/-i and x = +/-2isqrt5
D. x = +/-i and x=2sqrt2
Answer:
[tex]\large\boxed{B.\ x=\pm1\ and\ x=\pm2\sqrt2}[/tex]
Step-by-step explanation:
[tex]x^4-9x^2+8=0\\\\x^{2\cdot2}-9x^2+8=0\qquad\text{use}\ (a^n)^m=a^{nm}\\\\(x^2)^2-9x^2+8=0\\\\\text{substitute}\ x^2=t\geq0\\\\t^2-9t+8=0\\\\t^2-t-8t+8=0\\\\t(t-1)-8(t-1)=0\\\\(t-1)(t-8)+0\iff t-1=0\ \vee\ t-8=0\\\\t-1=0\qquad\text{add 1 to both sides}\\t=1\geq0\\\\t-8=0\qquad\text{add 8 to both sides}\\t=8\geq0[/tex]
[tex]t=x^2\to x^2=1\ \vee\ x^2=8\\\\x^2=1\Rightarrow x=\pm\sqrt1\to x=\pm1\\\\x^2=8\Rightarrow x=\pm\sqrt8\to x=\pm\sqrt{4\cdot2}\to x=\pm\sqrt4\cdot\sqrt2\to x=\pm2\sqrt2[/tex]
Answer:
Step-by-step explanation:
Given is the equation of 4th degree in x,
[tex]x^4 - 9x^2 + 8 = 0[/tex]
Substitute [tex]x^2=u[/tex]
[tex]u^2-9u+8=0\\(u-1)(u-8)=0[/tex]
u=1 and u =8
i.e. [tex]x^2=1\\x^2 =8[/tex]
Solving we get
[tex]x=1,-1,2\sqrt{2}, -2\sqrt{2}[/tex]
Option B is right.
what is the midpoint of the verticle line segment graphed below?
Answer:
C (2, -5/2)
Step-by-step explanation:
To find the midpoint of two points
mid = (x1+x2)/2, (y1+y2)/2
= (2+2)/2, (4+-9)/2
= 4/2, -5/2
=2,-5/2
Complete the square to solve the equation below x^2 + 10x - 13 = 17
Answer:
x = -12.42 or x = 2.42
Step-by-step explanation:
x^2 + 10x - 13 = 17
To solve this using the completing the square method, we will follow the steps below;
First, we will add 13 to both side of the equation, we want only the x variable to be on the left-hand side of the equation
x^2 + 10x - 13 + 13 = 17 + 13
x^2 + 10x = 30
The next step is to add both-side of the equation by square of half of the coefficient of x (that is ; half of 10 is 5, then we will add 5² to both-side of the equation)
x^2 + 10x + 5² = 30 + 5²
Then we can now factorize the left-hand side of the equation and at the same time simplify the right-hand side of the equation
(x + 5)² = 30 + 25
(x + 5)² = 55
We will then take the square root of both-side of the equation
√(x + 5)² = ±√55
x + 5 = ±√55
To get the value of x, we will subtract 5 from both-side of the equation
x + 5 - 5 = ±√55 - 5
x = ±√55 - 5
Either x = + √55 -5 = 7.42 -5 = 2.42
OR
x = -√55 - 5 = -7.42 - 5 = -12.42
Therefore either x = -12.42 or x = 2.42
x = -12.42 or 2.42
Type the correct answer in each box.
The value of x is °, and the value of y is
°.
Answer:
x = 60°, y = 50°Step-by-step explanation:
We know: the angles measures in a triangle add up to 180°.
(look at the picture)
z + 50 + 60 = 180
z + 110 = 180 subtract 110 from both sides
z = 70°
x + 50 + 70 = 180
x + 120 = 180 subtract 120 from both sides
x = 60°
Angles x, y and z are on one side of a straight line. Therefore they add to 180°.
x + y + z = 180
60 + y + 70 = 180
y + 130 = 180 subtract 130 from both sides
y = 50°
Answer:
x = 60°, y = 50°
Step-by-step explanation:
We know: the angles measures in a triangle add up to 180°.
z + 50 + 60 = 180
z + 110 = 180 subtract 110 from both sides
z = 70°
x + 50 + 70 = 180
x + 120 = 180 subtract 120 from both sides
x = 60°
Angles x, y and z are on one side of a straight line. Therefore they add to 180°.
x + y + z = 180
60 + y + 70 = 180
y + 130 = 180 subtract 130 from both sides
y = 50°
The cost function of an apple stand is C = 10n + 150, where n is the number of buckets of apples sold. The revenue function of this apple stand is r= 15n.
Create a graph to show each of these functions. According to your graph,
what is the break-even point for this apple stand?
A. n = 30
B. n = 10
C. n = 25
D. n = 14
Check the picture below.
Answer:
A. n = 30Step-by-step explanation:
The cost function is
[tex]C=10n+150[/tex]
Where [tex]n[/tex] is the number of buckets of apples sold.
The revenue is defined as
[tex]r=15n[/tex]
The image attached shows both functions graphed in the same coordinate system. According with the graph, the break-even point is at (30,450), that is, 30 of buckets sold and $450 of revenue and cost.
In other words, we need to sell 30 buckets to have the cost and revenue equals.
Therefore, the answer is A.
05.07) The net of a pyramid is shown below: The net of a square based pyramid, with bases labeled 7 inches and the height of the triangle labeled 14 inches. The surface area of the solid is ____ square inches. Numerical Answers Expected!
Answer: 245 [tex]in^{2}[/tex]
Step-by-step explanation:
You can find the Surface Area of a figure by adding up the areas of each shape.
First you have to find the area of the base.
7×7 = 49
Then you can find the area of the 4 triangles that complete the pyramid.
Formula for area of a triangle: [tex]\frac{1}{2} bh[/tex] (one half of base times height)
[tex]\frac{1}{2} (14*7) = x\\\frac{1}{2} 98 = x\\x = 49[/tex]
Since all the triangles are the same, you only have to calculate that once.
Now you just add everything together, and that's your surface area.
[tex]49+49+49+49+49= 245[/tex]
Please mark brainly if it helped you out!~
Answer: 245
Step-by-step explanation:
first you have to 7 for the square which = 14
then after that you do 1/2 b x h = 1/2 7 x 14= 3.5 x 14= 49 but then you have 4 triangles so 49 x 4=196. Then 49 + 196= 245
Find the value of a in the picture
Answer:
The measure of arc a is 86°
Step-by-step explanation:
we know that
The measure of the inner angle is the semi-sum of the arcs comprising it and its opposite.
so
86°=(1/2)[arc c+arc a]
see the attached figure with letters to better understand the problem
In this problem
Triangles ABO and CDO are congruent by SSS postulate theorem
∠AOB=∠COD
∠AOB=arc a -----> by central angle
∠COD=arc c -----> by central angle
therefore
The measure of arc a is congruent with the measure of arc c
arc a=arc c
so
86°=(1/2)[2arc a]
86°=[arc a]
arc a=86°
Sally is near the end of a three year lease on a car with an original MSRP of $38,000. Her leasing company claims that the car is now worth only $28,500. Which percentage represents the residual value of Sally’s leased car?
a.
25%
b.
33%
c.
67%
d.
75%
Answer:
Option D is correct.
Step-by-step explanation:
Original Price of car = $38,000
Current Price of car = $28,500
The residual value of Sally's leased car = x = ?
Residual value * Original Price = Current Price
x * 38,000 = 28,500
x = 28,500/38,000
x = 0.75
Since we need to find percentage
Multiply the residual value with 100 i.e,
0.75 * 100 = 75%
Option D is correct.